Improving the Performance of Educators and Education Personnel Seen from Office Layout, Work Experience and Teamwork at SMP Katolik Santo Paulus Singaraja - Lugrahini Safitri Dewi, Komang Dyah; Juli Nuryani, Ni Nyoman (Universitas Ibn Khladun Bogor, 2025)
This study was conducted with the aim of finding out how the arrangement of office space owned in the employee room can affect performance, the extensive work experience of each employee can help improve performance and good teamwork in working can affect the performance of educators and education personnel at SMP Katolik Santo Paulus Singaraja. The analysis technique in the study by knowing the value of each research instrument, be it validity test, reliability test, classical assumption test, multiple linear regression analysis, model feasibility test (Goodness Of Fit), hypothesis test. The research that has been conducted shows the impact of good office space arrangement is able to change employee habits in working, office layout has a positive impact and shows significant results on performance, from good office space arrangement will certainly greatly help employees in maximizing performance. The extensive work experience obtained from employee habits working in the agency from this has an influence on the performance results of each individual working at SMP Katolik Santo Paulus Singaraja, work experience has a positive influence and has a significant impact on the performance produced by employees, from the results of the study it can be said that the extensive work experience of each employee can affect their performance. Teamwork from each employee or individual in working has a positive impact on the results of employee work, good teamwork can certainly affect the performance of an employee who works at SMP Katolik Santo Paulus Singaraja, based on this, it can certainly be said that the better the cooperation carried out in working, the more it can help speed up the completion of the work .